Penerapan Model Problem Based Learning (PBL) Untuk Meningkatkan Motivasi Belajar Siswa Pada Pelajaran Matematika Di Kelas XII BKP SMK Negeri 14 Medan - Nora Yanti Gurning (KOLONI, 2024)
This research aims to examine the model of using problem based learning in increasing students' learning motivation in mathematics lessons in class XII BKP SMK Negeri 14 Medan. The problem examined in this research is the low learning motivation of students in mathematics lessons in class XII BKP SMK Negeri 14 Medan. This research is Classroom Action Research (PTK) which was carried out in 2 cycles, where in each cycle there were two meetings and each meeting lasted 2 x 40 minutes. In each cycle, an observation sheet will be given, and a questionnaire will be given at the beginning and end of cycle two to measure the level of student learning motivation. Based on the observation results, the results obtained in the first cycle of meeting I were that 6 students (26.08%) had high motivation, and 17 students (73.39%) had low motivation. In cycle I, meeting II, 4 students (17.39%) had very high learning motivation, 1 student (4.34%) had high learning motivation, 6 students (26.08%) had moderate learning motivation , and 12 students (52.17%) were not yet motivated. In cycle II, meeting I, 6 students (26.08%) had very high motivation to learn, 9 students (39.13%) had high motivation, 3 students (13.04%) had moderate motivation , 5 students (21.73%) were not motivated. In cycle II, meeting II there was data that 20 students (86.95%) had very high learning motivation, 1 student (4.34%) had high learning motivation, and 2 students (8.69%) were not yet motivated. Based on the results of this research, it can be concluded that using the Problem Based Learning model can increase student learning motivation in class XII BKP SMK Negeri 14 Medan